Estudio de factibilidad para la creación de una empresa asociativa para ofertar turismo artesanal en la ciudad de Otavalo - Acebo López, Analy Michelle (2015)
This project starts from the need to give to national and international tourist that to visit Otavalo city a new alternative to make tourism, with this they can know how are making the crafts, knowing the existence the artisans association UNAIMCO, where we found too many artisans associated that to make the crafts with different materials. The study about the market, offer us a general perspective about likes and preferences from the touristic, giving information that permit us to perform possible investments. As soon as the technical study we found the alternative to evaluate the attention capacity that can give to touristic. Through the results we are going to obtain the possibility to create the association that to offer a service from craft tourism. This permit us search things that to facilitate the inversion. The project have defined that will be finance the first part with own input and the second part by the National Foment Bank, because they offer us a low interest rate. The financial review tell us that a positive financial position can create such a good economic performance that allows us to contribute to the social development and the craftsmen who are ready to perform the demonstrations.